Navarre in the Archive of the Nobility (XII-XXth century) - Gómez Vozmediano, Miguel F. (Huarte de San Juan. Geografía e Historia, 2010)
The Nobility Section of the National Historical Archive was founded in 1988 to hold the files of noble origins which were received either by purchase or donation. The presence of nobility from early medieval times, above all in modern and contemporary eras, occupying high positions in the Administration and the Church, as well as their extensive matrimonial links, meant that many of the aristocratic titles had some relation to Navarre. The author identifies this documentation which makes reference to the exercising of political, military and religious responsibilities in the old kingdom or belonging to the hereditary management of their possessions.